Standardization of specific and non-specific parameters of sambiloto (Andrographis paniculata. Burm.f) ethanol extract as standardized herbal medicine - Heldi Candra; Indri Ayu Ningsih; Claudia Angelina Kurnia Bat (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
This study's objective is to ascertain how to make Sambiloto simplicia that is good and right according to the second edition of the 2017 herbal pharmacopoeia standards, to find out non-specific and specific parameters, which consist of tests for water content, ash content, drying shrinkage, water-soluble extract content, and extract content. Soluble ethanol in Sambiloto simplicia and knowing the secondary metabolites of Sambiloto simplicia. This study employed a qualitative and quantitative observational methodology. The research object was the Sambiloto plant (Andrographis paniculata. Burm.f) which was planted within the home's yard in the Sungai Lekop Plot, Sungai Lekop Village, Sagulung District, Batam City. The results showed that Sambiloto extract contains secondary metabolites of tannins, alkaloids, saponins, terpenoids and flavonoids. Sambiloto viscous extract obtained by 5 ml from 500 ml extract parameter values for non-specific and specific test water content of Sambiloto is 9%, drying shrinkage is 18.5%, total ash content is 10%, water-soluble extract is 12.96%, and ethanol-soluble extract 8%, specific and non-specific parameter tests met the requirements for the 2017 herbal pharmacopoeia, the results showed that Sambiloto simplicia fulfilled the requirements as a standardized herbal medicine.